2016
DOI: 10.1186/s13063-016-1601-0
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive therapy for psychological distress in pregnancy: study protocol for a randomized controlled trial

Abstract: BackgroundClinically significant psychological distress in pregnancy is common, with epidemiological research suggesting that between 15 and 25 % of pregnant women experience elevated symptoms of stress, anxiety, and depression. Untreated psychological distress in pregnancy is associated with poor obstetrical outcomes, changes in maternal physiology, elevated incidence of child physical and psychological disorders, and is predictive of maternal postpartum mood disorders. Despite the wide-ranging impact of ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 97 publications
(101 reference statements)
1
24
0
Order By: Relevance
“…Some of these behavior changes may be a direct result of increased stress and anxiety due to the pandemic. In general, up to one quarter (25 %) of women experience psychological distress during pregnancy which can lead to poor birth outcomes [ 22 , 23 ]. Stressful events also have significant deleterious effects on birth outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these behavior changes may be a direct result of increased stress and anxiety due to the pandemic. In general, up to one quarter (25 %) of women experience psychological distress during pregnancy which can lead to poor birth outcomes [ 22 , 23 ]. Stressful events also have significant deleterious effects on birth outcomes [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mental and physical discomfort may disrupt or even alter an individual's ability of awareness and nonjudgment [11,33]. Braeken et al reported pregnant women with lower emotional disorders have higher mindfulness during prenatal and postpartum periods [10].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression are the most common symptoms in the complex psychological changes during pregnancy [ 5 7 ]. Physical, pathological, and social changes, that leading to anxiety and depression will continue from the prenatal period to puerperium [ 8 , 9 ]. Thus, the most common female mental disorder, that is postpartum depression, refers to depression occurring during puerperium.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the most common female mental disorder, that is postpartum depression, refers to depression occurring during puerperium. Postpartum depression usually occurs 2 weeks after childbirth, and the symptoms are typical at 4–6 weeks [ 8 , 9 ]. Postnatal depression (PND) is often referred to a condition occurring after childbirth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation